KEBIJAKAN LUAR NEGERI REPUBLIK INDONESIA DALAM SENGKETA LAUT TIONGKOK SELATAN (ERA PRESIDEN SOEHARTO SAMPAI PRESIDEN JOKOWI) - Anna Yulia Hartati (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2016)
The objective of this study was to determine why Indonesia take a role in the form of foreign policy in the South China Sea dispute and to know the shapes of Indonesian foreign policy related to the dispute. Political constellation in the Asia Pacific region at the same colored grim situation heats up. South China Sea that becomes the fulcrum of geopolitics in the Asia Pacific region into an international level talks for causing triggering a conflict between a number of major countries in Asia and some member states of ASEAN. The core issue is around claims disputed border area (territorial zone). By the end of 2014, the South China Sea territorial disputes this has impacted quite dramatically towards polarization force the warring countries. Indonesia as one of the countries in Southeast Asia was not directly involved in the conflicts over territory in the South China Sea. However, Southeast Asia is a strategic land for Indonesia which has a number of potential regionality within ASEAN membership. In short, if the regional stability in the ASEAN body threatened by dispute in the South China Sea, then it will have an impact on the credibility and noncompliance with ASEAN security posture that would be influential for Indonesia. This study uses research instrument documentation, using techniques reseach library (library research), namely by taking the data from books, articles, and internet. Design in the design of this study was descriptive, whereas Comparative analysis using Constant (Grounded Theory Research). Keywords: Foreign Policy Affairs, Dispute LTS, National Interest Indonesia, stability of the region, ASEAN